Strategies in a corpus of simultaneous interpreting. Effects of directionality, phraseological richness, and position in speech event - Dayter, Daria (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
The study surveys the existing literature on strategies in simultaneous interpreting (understood here as transformations indicative of interpreting procedures that manifest in the product of interpreting). On the basis of the survey, a summary of eight strategies which are present in various research strands is compiled. I use a parallel bidirectional corpus of Ru-En simultaneous interpreting to extract a random sample of 360 fragments and investigate the presence of the eight strategies in the sample. The type of strategy is then correlated with three variables: direction of interpreting, position of the source fragment in the original text, and phraseological richness of the source fragment. The findings indicate that all the strategies, including an additional transformation category (incorrect interpretations), are present in the sample, although some of them are considerably less common than earlier literature purports. All three variables have significant association with the type of strategy, although in cases of directionality this holds only for saucissonnage and omission. A close analysis of three coding categories—omission, explicitation, and incorrect interpretations—suggests that interpreters in this corpus orient more towards a performative than informative function of their SI.